Working Capital Management and Its Impact on the Financial Performance of Listed Manufacturing Companies on the Ghana Stock Exchange - ASHUN, ANTHONY KWESI; Abass Sagoe, Alhassan; Abubakar, Sani (Southeast Asian Business Review, 2026)
The study seeks to investigate how working capital management affects the financial performance of manufacturing companies listed on the Ghana Stock Exchange (GSE). The study used secondary data from the published financial statements of manufacturing companies listed on the Ghana Stock Exchange for the twelve years between 2011 and 2022. The study found that the financial performance of manufacturing companies listed on the Ghana GSE is significantly influenced by inventory management. Research has shown that the inventory turnover ratio has a significant impact on both return on equity and return on assets. However, the result showed that earnings per share and gross profit margin are negatively affected by inventory turnover management. The study also demonstrated that the return on equity, return on assets, and earnings per share of the manufacturing industry listed on the GSE are positively and significantly affected by the accounts receivable turnover ratio. The findings of the study showed that, during the period examined, the ratio of cash and cash equivalents significantly and favorably affected the gross profit margin, return on equity, return on assets, and cash and cash equivalents. The findings also demonstrated that earnings per share were positively impacted by GSE-listed manufacturing, cash, and cash equivalents. The study offers the following policy recommendations: It is recommended that management extend its inventory conversion time. The management of the companies investigated should not use unnecessary purchases to lock up capital. To boost their profitability, the management of the companies included in the study should continually promote initiatives that facilitate the acceleration of inventory turnover.